Evaluation of bone regeneration around implants with and without flap elevation - Sachin Sinha; Santosh Kumar; Priyanshu Ranjan Sonoo; Utkarsh Kumar; Rohit Siddhartha; Sanjay Kumar Singh (Wolters Kluwer Medknow Publications, 2021)
Background: The aim of this study is to clinically evaluate and compare the clinical success and the relative bone healing of the implants which are placed using a flapless procedure and compare it to those placed by the conventional flap technique. Materials and Methods: This study was conducted with ten patients that were randomly divided into two groups. Group A included patients with immediately placed implants after extraction with flap elevation. Group B included patients with immediately placed implants after extraction without any flap elevation. The clinical parameters recorded were Plaque index, Modified Gingival Index, Early Wound Healing Index, Buser's criteria, Distance between implant shoulder and the crestal bone (DIB), and Radiographic Examination in a standardized manner to evaluate changes for the DIB values. Results: There was an improvement in Plaque Score from baseline to 1 month and baseline to abutment placement (6 months), which was statistically significant, but the plaque score from 3 months to abutment placement (6 months) was statistically nonsignificant in both the group. There was an increase in modified gingival score from baseline to 3 months, baseline to abutment placement (6 months), and 3 months to abutment placement (6 months), which was statistically significant in both the groups. The DIB scores in Group A recorded at baseline to 6 months were 2.80 ± 0.57 and 1.90 ± 0.42, respectively, showing a mean difference of −0.90 and P = 0.001 in comparison. Whereas, the DIB scores in Group B at baseline to 6 months were 3.20 ± 0.57 and 2.50 ± 0.50, respectively, showing a mean difference of −0.70 and P = 0.001 in comparison. The DIC scores in Group A at baseline to 6 months were 1.60 ± 0.54 and 0.00 ± 0.00, respectively, showing a mean difference of −1.60 and P = 0.003 in comparison, Whereas the DIC scores in Group B at baseline to 6 months were 1.40 ± 0.54 and 0.00 ± 0.00, respectively, showing a mean difference of −1.40 and P = 0.005 in comparison. Conclusion: Implants placed in fresh extraction sockets with and without mucoperiosteal flap elevation can be successfully done with augmentation procedures. Short-term survival rates and clinical outcomes of both groups were similar and appeared to be predictable treatment modalities.